Detection of diatoms in a case of mud aspiration at a coastal area - Tsuneya, Shigeki; Nakajima, Makoto; Yoshida, Maiko; Hoshioka, Yumi; Chiba, Fumiko; Inokuchi, Go; Torimitsu, Suguru; Iwase, Hirotaro (Legal Medicine, 2024)
•Diatoms in non-drowned bodies are attributed to postmortem invasion or “natural load”•Contamination during autopsy or diatom testing are other diatom sources in such cases.•Sand around water bodies can be a possible diatom source in non-drowning cases.•Qualitative analysis help detect true drowning and false-positives in such cases.•Careful quantitative analyses may help establish the cause of death in non-drowning cases. The source of diatoms detected in non-drowned bodies have been attributed to postmortem invasion, contamination during autopsy or diatom testing, or “natural load.” However, sand aspiration has not been reported as a source. Herein, we report an autopsy case in which diatoms were detected in a non-drowned human who had aspirated mud. A man in his 60 s was found dead at a harbor park in Japan. His whole body was covered with sand, including his face. A situational investigation suggested that he may have entered the sea. Autopsy revealed intratracheal mud, with no obvious findings indicating drowning, suggesting that he died from mud aspiration probably due to hypothermia or non-lethal ethanol intoxication. In the diatom test, 10–100 diatoms/g were detected in bilateral lung samples, which were similar to those found in the intraoral and intratracheal mud and the sand samples from around the discovery site and not similar to those found in the seawater samples. The diatoms in the stomach content exhibited an intermediate trend between those found in the sand and seawater. Therefore, careful qualitative and quantitative analyses are required to differentiate between true drowning and false-positives in non-drowning cases to determine the cause of death.